2011
DOI: 10.1136/adc.2011.213702
|View full text |Cite
|
Sign up to set email alerts
|

The associations between ethnicity and outcomes of infants in neonatal intensive care units

Abstract: Neonatal growth characteristics and morbidity but not mortality are influenced by maternal ethnicity. Of concern is the risk of low Apgar scores in PAM infants and non-tertiary births of indigenous infants. Review of perinatal care for certain vulnerable ethnic populations is recommended due to the rapidly changing ethnic compositions of many countries around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…[18][19][20][21][22][23][24][25][26][27][28][29] Interestingly, there is increasing evidence that ethnicity may be an independent risk factor for the development of severe ROP. [30][31][32][33] However, no North American studies on IGF-1 and ROP have been reported to our knowledge.…”
mentioning
confidence: 95%
“…[18][19][20][21][22][23][24][25][26][27][28][29] Interestingly, there is increasing evidence that ethnicity may be an independent risk factor for the development of severe ROP. [30][31][32][33] However, no North American studies on IGF-1 and ROP have been reported to our knowledge.…”
mentioning
confidence: 95%
“… 8 , 9 When compared with women of other ethnic backgrounds, Black women are 3–4 times more likely to have a very early preterm birth, 10 , 11 and ethnic differences in neonatal respiratory morbidity have been reported. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Previous literature had shown a difference in outcomes, particularly in a regional setting . Studies at more urban centres have more recently shown no difference in outcome by Indigenous status, but this is the first study with a large Aboriginal and Torres Strait Island population, which serves very remote areas, to show the same outcome. A total of 38.3% of extremely preterm babies in this study were of Aboriginal and/or Torres Strait Islander origin, which is much higher than other Australian studies.…”
Section: Discussionmentioning
confidence: 65%